Pengaruh NIM, LDR, dan BOPO terhadap Profitabilitas Perbankan yang Tercatat di BEI Selama Pandemi - Citra Puspitasari; Fauziah Aprilia; Mentarie Mentarie; Mulia Saba Bilkis (Global Financial Accounting Journal, 2021)
This research aims to determine the effect of Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and Operational Cost to Operational Income (BOPO) towards Bank Profitability (Return on Equity) that listed on Indonesia Stock Exchange through Covid-19 pandemic in 2020 period. The population of data that used in this research are all banks listed on the Indonesian Stock Exchange. The sample selection in this research used a purposive sampling method with 3 criteria, so 14 banks with a higher amount of equity have been selected as a samples. Using the financial statement from quarter 1 until quarter 4 in year 2020, so the sample that will be tested amount as 56 data. The data analysis method in this research is multiple regression analysis using the SPSS version 16 application program. The research shows the result that NIM and BOPO did not have an effect to bank profitability (ROE), while LDR has negative effect to ROE. Where NIM, LDR, and BOPO simultaneously have an effect on ROE of 57.1% while the remaining 42.9% is influenced by other variables which are not used in this research.